EFEK KATEKIN DAUN GAMBIR (UNCARIA GAMBIR ROXB) TERHADAP KADAR MALONDIALDEHID SERUM DAN EKSPRESI GEN SIRTUIN 1 PADA HIPOKAMPUS MENCIT BETINA MODEL PENUAAN - Situmorang, Novrina; ., Zulham; Feryawati, Lita (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2021)
Aging is a physiological process characterized by progressive loss of physiological integrity that leads to impaired function and increased susceptibility to death. Oxidative stress is one of the factors that cause aging due to an imbalance between the amount of oxidants and antioxidants. In oxidative stress condition, malondialdehyde levels increase. D-galactose can induce aging in various organ systems. D-galactose induces oxidative stress in various organs through increased production of reactive oxygen species (ROS) and advanced glycation endproducts. In oxidative stress condition, sirtuin1 (Sirt1) produces ribose O-acetyl-ADP which, later, is reduced into ribose ADP. Both of them have a protective effect against oxidative stress. Consumption of antioxidants may prevent aging. Gambir contains health-promoting ingredients such as catechins. This study aims to determine the effect of gambier leaves catechin extract on serum malondialdehyde levels and the expression of sirtuin 1 gene in female mice aging model induced by d-galactose. This is an in vivo experiment with post test-only control group study. The samples were 28 female mice which were divided into 4 groups namely P0, P1, P2, and P3. Each group was injected 150 mg/kgBW d-galactose intraperitoneally. P1, P2, and P3 were treated orally with 100, 200, and 400 mg/kgBW gambir leaves catechin extract, respectively. Statistical test use descriftive analisys. There were significant differences in serum MDA levels in all groups (p=0.002) and there were significant differences between the P0 and P2 groups (p=0.010) and between the P0 and P3 groups (p=0.010). Sirtuin1 gene relative expressions decresead in P1 (0,49), P2 (0,74), and P3 (0,43) as compared to P0 (1.00). Conclusion. Gambir leaves catechin extract reduces serum malondialdehyde levels in aging mouse models induced by d-galactose with an optimal dose of 200mg/kgBW. and cannot reduce the relative expression of Sirt1